How Does AI Improve Coronary Artery Disease Detection? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2015)
Coronary Artery Disease (CAD) remains a leading cause of morbidity and mortality worldwide, presenting a significant challenge to healthcare professionals. T...
Keywords: AI in Cardiology; Improve; Coronary; Artery; Artificial Intelligence; Machine Learning; Deep Learning